PEMANFAATAN MEDIA PROYEKTOR DALAM MENINGKATKAN MINAT DAN KEAKTIFAN BELAJAR SISWA KELAS VIII AISYAH (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article discusses the use of projector media to increase learning interest and classroom participation of students in class VIII Aisyah at PPS Utsman Bin Affan Batam. The article was prepared based on field experience during the School Field Introduction Program (PLP) conducted from 5 January to 18 February 2026. The study used a descriptive qualitative approach through observation, teaching practice, documentation, and reflection on classroom activities. The data show that the school has three projectors used to support learning. In grade 8 learning activities, the use of visual media helped present material in a clearer and more systematic manner, attracted students' attention, and made question-answer and discussion sessions more lively. In class VIII Aisyah, students showed good enthusiasm during interactive learning, and about 85% of students were able to understand the material delivered. These findings indicate that projector media can function as an effective supporting medium to foster students' interest, focus, and activeness in learning.